Rational use of land resources in the mining industry during the placement of overburden rocks - Kuantay, A.; Babii, K. V. (НТУ ДП, 2022)
Land resources are fundamental in the territory of each state, therefore they are subject to strict accounting and control. As a result of the activities of mining enterprises for the extraction of coal, ferrous and non-ferrous metals, building materials, etc., the land fund is experiencing the greatest impact and changes.
Keywords: rational